Bibliometric Analysis of Thyroid Research Publications in Asian Countries - R. , Abhilash Babu; Uma Devi, L.N. (International Journal of Psychosocial Rehabilitation, 2020)
The current scenario of thyroid malignancy has been increasing over the last four decades. The present study analysis is aiming to explore the factors causing the formation of various thyroid cancers and to spot out people with thyroid issues. The study aims to analyze the publications of thyroid malignancy on account of year, document type, author collaboration, journals, country, language, institution, and word-wise characteristics, mainly concentrating on Asian countries. The study found that the year-wise output in the year 2015 witnessed 17.77% data, which rapidly increased to 20.03% by the year 2019. It reveals that the majority of articles are written by co-authors. It reveals that China ranks at the top (5229/42.1%) with the majority of the publications output of Thyroid Research Contribution, followed by South Korea (1887/15.2%), Japan (1362/11%), Turkey (1231/909%), followed by India (721/5.8%), Iran, Taiwan, Israel, Pakistan, and Saudi Arabia, respectively.